If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -11 = 9x + -15 Reorder the terms: -11 + 5x = 9x + -15 Reorder the terms: -11 + 5x = -15 + 9x Solving -11 + 5x = -15 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -11 + 5x + -9x = -15 + 9x + -9x Combine like terms: 5x + -9x = -4x -11 + -4x = -15 + 9x + -9x Combine like terms: 9x + -9x = 0 -11 + -4x = -15 + 0 -11 + -4x = -15 Add '11' to each side of the equation. -11 + 11 + -4x = -15 + 11 Combine like terms: -11 + 11 = 0 0 + -4x = -15 + 11 -4x = -15 + 11 Combine like terms: -15 + 11 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| -(8x-4y-7)= | | (y-3)(y-5)=0 | | 102-7x=11x+16 | | -5x=2 | | -8=.40z+4 | | .60p-.5=.70 | | .60p-.5= | | 4+x=7 | | (y-1)(y-3)=0 | | 6-9x=171-44x | | 6x-9=51 | | 12x^2-9=0 | | 49-5x=22x+19 | | 5x+10=-32-9x | | p(x)=-2x^2+120x-788 | | 6-8x=86-36x | | 63x^4+37x^2+4=0 | | -8k=7.7-7.2k | | 5x+31=14x-50 | | 0=x^3+2x^2+8x | | 2e-8= | | 3-ax+4x-36=0 | | x=5-y | | p=3 | | 7=0.5b+2.5 | | 15y+5y-6=17y | | 6y=y-23 | | 4x^2-12x+9=9 | | 12m-9=14m | | 12m-9=14 | | 2x+7=7x+2 | | 7(1-p)=-3(5+3q) |